Keragaman Nematoda Parasit Tumbuhan Pada Pertanaman Jambu Biji Kristal (Psidium guajava L.) di Pasuruan dan Lampung - Fitriyani, Novi Nur; Windriyanti, Wiwin; Widayati, Wiludjeng; Swibawa, I Gede; Aeny, Titik Nur (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2023)
The purpose of this study was to determine the plant parasitic nematodes associated with crystal guava plantations in Pasuruan and Lampung. Soil samples was taken from crystal guava plantations in Pasuruan and Lampung. Extraction and observation of nematodes was carried out at the Laboratory of Plant Pest Science, Department of Plant Protection, Faculty of Agriculture, Lampung University in November 2022-January 2023. The extraction method used filtering and centrifugation with a sugar solution. Identification based on morphological characteristics to genus level. The study identified 15 genera of parasitic nematodes, namenly Radopholus, Meloidogyne, Heterodera, Criconemoides, Xiphinema, Aphelenchus, Aphelenchoides, Tylenchulus, Tylenchus, Tylenchorynchus, Rotylenchus, Rotylenchulus, Ditylenchus, Pratylenchus, and Scutellonema. The nematodes with the highest populations were Criconemoides in Pasuruan and Radopholus in Lampung.